Web Based Security System Academic Exam Questions Using Advanced Encryption Standard - Bagus Satrio Waluyo Poetro; Sam Farisa Chaerul Haviana; Arief Budiman (Journal of Applied Science and Technology, 2021)
One way to measure the success of the academic process and achievement of student competence, is giving exams, from the smallest level namely daily tests, semester exams, to the highest level, namely the national exam. In an effort to maintain the security of exam question data, there is a data security method known as cryptography. In this research, a security system was designed that serves to protect exam questions so that data cannot be read by student before its time by using the Advanced Encryption Standard (AES) algorithm.  The AES algorithm is a type of symmetric algorithm where the encryption and decryption processes have the same key for the encryption and decryption processes. In the system that will be designed, the Caesar Cipher algorithm is used to form an additional key (seed) that is kept secret from the public. The results of this study indicate that AES encryption method can give results maximum so that the AES method can applied to virtual data storage system to protect the transmitted data.